AB0107 Regulation of the Expression of Runx2 in Human Osteoarthritis Osteoblasts with SP, IGF-1 and TNF-Alpha: An in Vitro Study. (9th June 2015) - Perniola, S.; Natuzzi, D.; Lacarpia, N.; Bizzoca, R.; Venerito, V.; Moretti, B.; Notarnicola, A.; Maccagnano, G.; Lapadula, G.; Iannone, F.
Abstract : Background: The protein Runt-relatede Transcription Factor 2 (Runx2) promotes the expression of most genes of the bone matrix proteins at the early stage of osteoblast differentiation, leading the cells to acquire an osteoblastic phenotype. Runx2 interacts with the Transforming Growth Factor β (TGF-β) and Bone Morphogenetic Proteins (BMPs) pathways. Furthermore, Runx2 interactions with the Wnt/β-catenin canonical way promote the osteoblastic differentiation of the mesenchymal cells. It is established that the Insulin-like Growth Factors (IGFs) and the Tumor Necrosis Factor α (TNF-α) regulate the Runx2 expression in osteoblasts at different stages of differentiation. Instead there are no studies about the role of P Substance (SP), IGF-1 and TNF-α in the regulation of the expression of Runx2 in the human OA osteoblasts. Objectives: To evaluate the in vitro expression of Runx2 in human osteoblasts from normal and OA knees after the stimulation with SP, IGF-1 and TNF-α. Methods: Osteoblasts have been obtained from human knees of 4 OA patients (2 women, 2 men) undergoing surgery replacement and 5 healthy donors (HD) (2 women, 3 men) with joint traumatic fracture. The osteoblasts were cultured until reaching confluence. At sub-confluence of the third passage, osteoblasts were cultured in one of the following conditions for 24 hours: without any stimulus, with SP (100 μM), with IGF-1 (100 ng/mL) or with TNF-α (10ng/mL). After stimulation, analysis of the expression of Runx2 was carried out by western blotting and immunocytochemistry. Statistical analysis was performed by IBM SPSS 20 analysis software, using Wilcoxon signed-rank and Mann–Whitney U tests. Multivariate logistic regression techniques were used to adjust for gender. Results: We compared the percentages of expression of Runx2 into the HD and OA groups: no statistically significant difference in the Runx2 expression after the stimulation with the SP was found in both groups, while a statistically significant increase with IGF-1 and TNF-α in HD group (p: 0.08 and 0.043 respectively). In the OA osteoblasts, we found a tendency to decrease the Runx2 expression with IGF-1 and TNF-α (p: 0.068 for both). The comparison HD vs OA showed a non-statistically significant difference between basal values and after the stimulation with SP (p: 0.086) while we found a statistically significant difference with IGF-1 and TNF-α (p: 0.014 for both). We did not find any influence of gender in Runx2 expression. The immunocytochemistry confirmed the findings of Western Blot analysis. Conclusions: This study provides evidence that IGF-1 and TNF-α are involved in the regulation of the expression of Runx2 in both normal and OA osteoblasts. However, Runx2 pathway seems to be disregulated in OA suggesting an abnormal osteoblastic differentiation occurs in OA bone. Disclosure of Interest: None declared